Hands-On AWS Penetration Testing with Kali Linux : Set up a Virtual Lab and Pentest Major AWS Services, Including EC2, S3, Lambda, and CloudFormation.: Set up a Virtual Lab and Pentest Major AWS Services, Including EC2, S3, Lambda, and CloudFormation. (2019) - Unknown
No abstract available